Radical planes? 9/11 and patterns of continuity - Mohr, Dunja M., 1968-; Däwes, Birgit (Costerus., 2016)
Radical Planes? 9/11 and Patterns of Continuity explores the intersections between narrative disruption and continuity in post-9/11 narratives from an interdisciplinary transnational perspective, foregrounding the transatlantic cultural memory of 9/11. Contesting the earlier notion of a cataclysm that has changed "everything," and critically reflecting on American exceptionalism, the collection offers an inquiry into what has gone unchanged in terms of pre-9/11, post-9/11, and post-post-9/11 issues and what silences persist. How do literature and performative and visual arts negotiate this precarious balance of a pervasive discourse of change and emerging patterns of political, ideological, and cultural continuity?